The Effect of Professional Skeptism, Forensic Accounting Knowledge, and Red Flags on The Ability to Detect Fraud with Organizational Culture as a Moderating Variable - Reski Anggreani; Syamsuddin Syamsuddin; Amiruddin Amiruddin; Asnawir `Asnawir (International Journal Of Economics Social And Technology, 2026)
This study examines the effect of professional skepticism, forensic accounting knowledge, and red flags on auditors’ fraud detection ability, with organizational culture as a moderating variable. While prior research has investigated these predictors individually, few studies have tested organizational culture as a boundary condition that determines when auditors’ competencies translate into effective fraud detection within Indonesia’s public-sector audit institutions; this gap motivates the present study. The novelty of this study lies in jointly modeling organizational culture as a moderator across three distinct auditor-level predictors within a single Attribution Theory framework, distinguishing it from prior research that examined alternative moderators such as auditor training or whistleblowing systems. Fraud detection ability is a critical competency required to ensure audit quality and accountable governance. Using a quantitative approach, data were collected through questionnaires from 130 auditors at the Representative Office of the Audit Board of the Republic of Indonesia (BPK RI) in South Sulawesi, selected through purposive sampling, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that professional skepticism and forensic accounting knowledge have significant positive effects on fraud detection ability, whereas red flags do not have a significant direct effect. Organizational culture significantly strengthens the effects of professional skepticism and forensic accounting knowledge on fraud detection ability, but it does not significantly moderate the relationship between red flags and fraud detection ability. These findings indicate that an organizational culture emphasizing integrity, transparency, and accountability enhances the effectiveness of auditors’ individual competencies, although it does not substitute for the technical judgment needed to act on warning signals alone. Theoretically, this study extends Attribution Theory by showing that organizational context conditions the influence of auditors’ internal attributes on fraud-related judgments. Practically, it offers BPK RI and similar public-sector audit institutions an evidence base for pairing competency development with deliberate cultural reinforcement to strengthen fraud detection in public financial audits.